Guidelines for the Treatment of Laryngeal Cancer from the Korean Society of Head and Neck Surgery - Jeon Yeob Jang; Geun-Jeon Kim; Sang-Yeon Kim; Min-Su Kim; Dong Kun Lee; Minsu Kwon; Dongbin Ahn; Myung Jin Ban; Young Kang; Ho-Ryun Won; Jae Won Chang; Dong Won Lee; et al. (Clinical and Experimental Otorhinolaryngology)
Objectives. Effective treatment of laryngeal cancer requires clinical decision-making that balances survival outcomes with the preservation of essential functions, such as voice and swallowing. This study, led by the Clinical Practice Guideline Committee of the Korean Society of Head and Neck Surgery, aims to establish evidence-based recommendations to guide surgeons in optimizing treatment decisions for patients with laryngeal cancer. Methods. A literature search was performed in the PubMed, Embase, Cochrane Library, and KoreaMed databases by a literature search expert and subsequently reviewed by a panel of 39 committee experts. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) method was employed to assess the quality of evidence and develop and report the recommendations. The strength of each recommendation reflects the guideline panel’s confidence that the benefits of an intervention outweigh its risks for the target population. After drafting the guidelines, Delphi questionnaires were distributed to members of the Korean Society of Head and Neck Surgery and an external reviewer panel. Results. In total, 15 evidence-based recommendations are provided, addressing six critical aspects of laryngeal cancer treatment: early-stage treatment, treatment of locally advanced cancer, neck management, adjuvant therapy, swallowing rehabilitation, and salvage treatment for recurrent tumors. Conclusion. The guidelines provide evidence-based, validated recommendations to support clinicians in making optimal treatment decisions for laryngeal cancer.